Learning Strategies Used By The Students Of English Department Of Tarbiyah Faculty At STAIN Palopo - Nurhidayah J (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
AbstractThe objectives of this research were: (1) to find out of the six learning strategies, which learning strategies applied by high achievers of English Department of Tarbiyah Faculty at STAIN Palopo; (2) to find out the most frequently strategies used  by the students of English Department of Tarbiyah Faculty at STAIN Palopo; (3) to find out differences between high achievers and low achievers in their learning strategies. In analyzing the data, the researcher applied quantitative method. The subject was the sixth semester students of English Department STAIN Palopo. This research used questionaire SILL as instrument. The result of the research showed that (1) the strategies applied by high achievers in memory strategy was “review English lessons”. In the cognitive strategies applied “trying to talk like native speakers‟. In the compensation strategies  “using synonym in case they couldn’t think of a word”. The high achievers always or almost always used all metacognitive strategy. They applied “try to find how to be a better learner”. In affective strategy “talk to someone else about how I feel‟. In social strategy applied “ask others to speak slowly or repeat” if they do not understand something in second language. (2) Metacognitive strategies is the most frequently strategy used by sixth semester students of English Department of STAIN Palopo with mean 3.3755. (3) There is a significant different in using language learning strategies between high achievers and low achievers. The highest frequently used by high achievers is metacognitive strategies and the lowest frequently used is memory strategies. Meanwhile, the highest frequently used by low achievers is affective strategies and the lowest frequently used is memory strategies.